Absorption of anthocyanins through intestinal epithelial cells - Putative involvement of GLUT2 - Ana Faria (2009)
Anthocyanins bioavailability is a major issue regarding their biological effects and remains unclear due to few data available on this matter. This work aimed to evaluate the absorption of anthocyanins at the intestine using Caco-2 cells. Anthocyanin extract, rich in malvidin-3-glucoside, was obtained from red grape skins and tested on Caco-2 cells. The absorption of anthocyanins, in absence or presence of 1% ethanol, was detected by HPLC/DAD/LC-MS. Our results showed that this transport was significantly increased in the presence of ethanol especially after 60 min of incubation. In addition, cells that were pretreated for 96 h with anthocyanins (200 mu g/mL) showed an increase of their own transport (about 50% increase). Expression of glucose transporters sodium-dependent glucose transporter 1, facilitative glucose transporters 5, and facilitative glucose transporters 2 was assessed by RT-PCR. It was found that facilitative glucose transporters 2 expression was increased (60%) in Caco-2 cells pretreated with anthocyanins, by comparison with controls. When the effect of anthocyanin extract on (3)H-2-deoxy-D-glucose uptake was tested, an inhibitory effect was observed (about 60% decrease). However, the malvidin aglycone was tested and had no effect. In conclusion, anthocyanins could be absorbed through Caco-2 cells, and can interfere with their own transport and also with glucose intestinal uptake.